Delineating groundwater contamination risks in southern coastal metropoles through implementation of geochemical and socio-environmental data in decision-tree and geographical information system. (1st February 2022) - Bertrand, Guillaume; Petelet-Giraud, Emmanuelle; Cary, Lise; Hirata, Ricardo; Montenegro, Suzana; Paiva, Anderson; Mahlknecht, Jürgen; Coelho, Victor; Almeida, Cristiano
Highlights: Integrated urban water management require spatialized contamination risk assessment. Combination of hydrochemical tracers and socio-environmental indicators is proposed. Decision tree building allows finding rules favoring types of quality alteration. Main factors are distance from sea and channels, population densities, social inclusion. Abstract: Due to global warming and local anthropogenic pressures, sustainable groundwater resource exploitation in coastal cities is increasingly threatened. For example, the fifth largest Brazilian city, Recife, is considered as a representative hot spot for these issues and illustrates the great challenges facing many urban areas in the southern hemisphere. There, recharge as well as surface water and groundwater quality are altered by frequent droughts and poorly planned environmental management since decades. To maintain access to water, thousands of private wells were dug in order to pump water from the multi-layered aquifer system found under the city. This massive exploitation is causing a chronic lowering of the water levels, as well as seawater intrusion and contaminations by wastewater or polluted surface waters. Through hydrochemical characterization, mainly Cl/Br ratio and Cl concentrations, of wells sampled throughout the metropole, this study first characterizes the main environmental impacts on the resource, i.e. waste waters and seawater. Combining this evaluation with lithological, land-use and socio-environmental data, it was then possible to build decision trees identifying combinations of multiple factors possibly having an impact on contamination types. The well and population densities, the waste and sewage management, as well as the absence of sanitary facilities in houses appeared as critical parameters to target in order to reduce the risk of contamination of the water resource and ensure its preservation. Based on these factors, we created a risk map for contamination types that should help in identifying areas where groundwater resource may present an environmental (and then health) issue for people. Besides, this study shows that the combination of hydrochemical, geomorphological and socio-environmental characterizations of these urban systems featuring very contrasted situations between neighborhoods is a relevant tool to propose further groundwater management strategies. Graphical abstract: Image, graphical abstract